PUBERTE VE ÜREMENİN NÖROENDOKRİN KONTROLÜNDE KİSSPEPTİN, RFRP-3 VE NESFATİN-1'İN ETKİLEŞİMİ ÜZERİNE DENEYSEL ARAŞTIRMALAR - ŞAHİN, ZAFER (Fırat Üniveristesi, 2015)
Araştırmamızda kisspeptin ve nesfatin-1'in dişi sıçanlarda üreme fonksiyonu ve enerji rezervi üzerine etkisinin yanı sıra RF9'un (RFRP3/GnIH antagonisti) ve p234'ün (kisspeptin reseptör (kiss1r) antagonisti) modülatör etkisinin belirlenmesi amaçlanmıştır. Bunun için 21 günlük sütten kesilmiş Spraque-Dawley dişi yavru sıçanlar kullanılmıştır. Hayvanlara intraserebroventriküler (ICV) enjeksiyon için kanüller anestezi altında takıldıktan sonra, 23. günden 60. güne kadar, kisspeptin, kisspeptin+p234, p234, RF9, RF9+p234, nesfatin-1 ve nesfatin-1+p234 günlük ICV olarak enjekte edilmiştir. Kisspeptin, RF9 ve nesfatin-1'in LH salgılanmasını artırdığı, p234'ün tek başına bazal LH düzeyine etki etmediği fakat kisspeptin, RF9 ve nesfatin ile birlikte uygulandığında ise LH düzeyinin anlamlı şekilde düştüğü görüldü. Kisspeptin, RF9 ve nesfatin uygulanan hayvanlarda pubertenin morfolojik işareti olan vajinal açıklığın erken başladığı, p234 ile geciken pubertenin kisspeptin, RF9 ve nesfatin-1 ile kombine edildiği gruplarda ise kontrol grubu ile aynı seviyeye döndüğü tespit edildi. Kisspeptin ve nesfatin gıda alımında azalma ve canlı ağırlık artışını azaltıcı etki oluştururken, RF9'un ise canlı ağırlık artışına etki etmeksizin gıda alımında azalma meydana getirdiği görüldü. Bu veriler, kiss1r antagonisti p234 ile kisspeptinin yanı sıra, ilk kez, GnIH/RFRP-3 antagonisti RF9'un ve kısmen nesfatin-1'in gonadal aks ve enerji rezervinin düzenlenmesiyle ilgili etkilerinin değiştirilebildiğini göstermektedir.

The aim of this study was to determine the modulatory effect of p234 (an antagonist of kisspeptin receptor (kiss1r)) and RF9 (an RFamide-related peptide-3 (RFRP3/GnIH) antagonist) on kisspeptin and, nesfatin-1- induced changes in reproductive functions and energy balance in the female rats. The prepubertal Sprague-Dawley female rats were weaned on day 21. The animals were intracerebroventricularly (ICV) cannulated under general anesthesia on postnatal 23 ages. Groups of female rats injected with kisspeptin, nesfatin-1, RF9, peptide 234, or kisspeptin plus p234, nesfatin plus p234 and, RF9 plus p234, daily (from 23 to 60 postnatal days). Kisspeptin, nesfatin-1 and, RF9 elicited significant elevations of circulating LH levels. Coadministrations of kisspeptin, nesfatin-1 and, RF9 with p234 decreased LH levels significantly. P234 alone did not cause any significant change in LH secretion. Kisspeptin, RF9 and, nesfatin-1 advanced vaginal openning (VO), which was delayed by kisspeptin antagonist. In the rats given kisspeptin plus p234, nesfatin-1 plus p234 or RF9 plus peptide 234, VO was not different from control rats. Kisspeptin and nesfatin-1 decreased both food intake and body weight while RF9 decreased only food intake without affecting body weight. The effects of kisspeptin and RF9 on energy balance were also reversed by central administration of p234. In conclusion, these results shows that it can be modulated as well as kisspeptin with kiss1r antagonist p234, for the first time, GnIH / RFRP-3 receptor antagonist RF9 and partly nesfatin-1 the effects related to the regulation of gonadal axis and energy balance.
Experimental studies on interaction between kisspeptin, RFRP-3- and, Nesfatin-1 in neuroendocrine regulation of the puberty and reproduction
Keywords: Fizyoloji